Salicylic Acid and N-Hydroxypipecolic Acid at the Fulcrum of the Plant Immunity-Growth Equilibrium - Shields, Alyssa; Shivnauth, Vanessa; Castroverde, Christian Danve M. (Frontiers in Plant Science, 2022)
Salicylic acid (SA) and N-hydroxypipecolic acid (NHP) are two central plant immune signals involved in both resistance at local sites of pathogen infection (basal resistance) and at distal uninfected sites after primary infection (systemic acquired resistance). Major discoveries and advances have led to deeper understanding of their biosynthesis and signaling during plant defense responses. In addition to their well-defined roles in immunity, recent research is emerging on their direct mechanistic impacts on plant growth and development. In this review, we will first provide an overview of how SA and NHP regulate local and systemic immune responses in plants. We will emphasize how these two signals are mutually potentiated and are convergent on multiple aspects—from biosynthesis to homeostasis, and from signaling to gene expression and phenotypic responses. We will then highlight how SA and NHP are emerging to be crucial regulators of the growth-defense balance, showcasing recent multi-faceted studies on their metabolism, receptor signaling and direct growth/development-related host targets. Overall, this article reflects current advances and provides future outlooks on SA/NHP biology and their functional significance as central signals for plant immunity and growth. Because global climate change will increasingly influence plant health and resilience, it is paramount to fundamentally understand how these two tightly linked plant signals are at the nexus of the growth-defense balance.